2020
DOI: 10.1002/qj.3890
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the robustness of multidecadal variability in Northern Hemisphere wintertime seasonal forecast skill

Abstract: Recent studies have found evidence of multidecadal variability in Northern Hemisphere wintertime seasonal forecast skill. Here we assess the robustness of this finding by extending the analysis to a diverse set of ensemble atmospheric model simulations. These simulations differ in either the numerical model or type of initialisation and include atmospheric model experiments initialised with reanalysis data and free-running atmospheric model ensembles. All ensembles are forced with observed sea-surface temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The predicted seasonal mean PNA index is calculated based on the monthly mean 500 hPa geopotential height prediction in December, January, and February (DJF), that is, with a 2‐month lead time. To be consistent with previous studies (e.g., O’Reilly et al., 2017, 2020; Weisheimer et al., 2020), the PNA index is defined by using the pointwise method (Wallace & Gutzler, 1981), that is, a linear combination of the normalized 500 hPa geopotential height anomalies ( Z ) at the four active centers: PNA = 1/4[ Z (20°N, 160°W) − Z (45°N, 165°W) + Z (55°N, 115°W) − Z (30°N, 85°W)]. Consistent results are obtained if the PNA index is defined as the time series associated with the second leading rotated empirical orthogonal function pattern (Barnston & Livezey, 1987; Van Den Dool et al., 2000) of the 500 hPa geopotential height anomalies in the Northern Hemisphere.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The predicted seasonal mean PNA index is calculated based on the monthly mean 500 hPa geopotential height prediction in December, January, and February (DJF), that is, with a 2‐month lead time. To be consistent with previous studies (e.g., O’Reilly et al., 2017, 2020; Weisheimer et al., 2020), the PNA index is defined by using the pointwise method (Wallace & Gutzler, 1981), that is, a linear combination of the normalized 500 hPa geopotential height anomalies ( Z ) at the four active centers: PNA = 1/4[ Z (20°N, 160°W) − Z (45°N, 165°W) + Z (55°N, 115°W) − Z (30°N, 85°W)]. Consistent results are obtained if the PNA index is defined as the time series associated with the second leading rotated empirical orthogonal function pattern (Barnston & Livezey, 1987; Van Den Dool et al., 2000) of the 500 hPa geopotential height anomalies in the Northern Hemisphere.…”
Section: Methodssupporting
confidence: 89%
“…The predicted seasonal mean PNA index is calculated based on the monthly mean 500 hPa geopotential height prediction in December, January, and February (DJF), that is, with a 2-month lead time. To be consistent with previous studies (e.g., O'Reilly et al, 2017O'Reilly et al, , 2020Weisheimer et al, 2020), the PNA index is defined by using the pointwise method (Wallace & Gutzler, 1981), that is, a linear combination of the normalized 500 hPa geopotential height anomalies (Z) at the four active centers:…”
Section: Methodsmentioning
confidence: 99%
“…natural forcings in the period 1920-1960 (Takemura et al 2006), where the weakest correlations are found in the historical ensemble, could also play a role. Also, it has been suggested that such non-stationarity can be due to a weakened influence of the El Niño-Southern Oscillation during the middle of the 20th century (O'Reilly et al 2020;Rieke et al 2021).…”
Section: B the Temporal Non-stationarity Of Correlationsmentioning
confidence: 99%
“…These pioneering results merit closer examination in experiments that explicitly target the multiyear timescale. Recent work has identified robust multidecadal modulations of seasonal prediction skill (Weisheimer et al, 2017;O'Reilly et al, 2020), which suggests that a focused multiyear prediction framework could shed further light on important interactions between seasonal, interannual, and decadal processes (e.g., the state dependence of multiyear predictability of seasonal climate) that would otherwise remain obscure. As a result of the signal-tonoise paradox (Scaife and Smith, 2018), a large ensemble size appears to be a prerequisite for skillful interannual predictions of some impactful atmospheric variations such as the NAO (Dunstone et al, 2016(Dunstone et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%